A STUDY OF WINE FERMENTATION FROM MUCILAGE OF COCOA BEANS (Theobroma cacao L.) - Nguyễn Thị Thanh Tịnh; Nguyễn Tiến An; Hồ Thị Thu Hòa; Nguyễn Thị Tươi (Tạp chí Khoa học Đại học Đà Lạt)
Cocoa mucilage, a by-product of cocoa beans processing, constitutes 10% of total cocoa beans, with soluble solids up to 17.78oBx, pH of 3.43 – 3.5, rich in sugar, minerals, organic acids and phenolic compounds. The aim of this research is to ferment cocoa bean mucilage to produce a beverage with alcohol concentration of 11.2%. The fundamental microorganism for ethanolic fermentation is Saccharomyces cerevisiae with a density of 2x107cfu/ml in conjunction with 1% (w/v) of commercial fermentation powder product. The product of fermentation was assessed in terms of ethanol concentration, and optimum primary fermentation conditions were at the temperature of 28oC with the duration of 7 days. Secondary fermentation, which helped in stabilizing the quality of wine, occurred at 18oC for 30 days. The final product attribute is warm orange to bright rust in color, transparent, with a distinct aroma and sensory assessment according to TCVN 3215-79 and 3217 – 79 achieving a good score of 16.39. Therefore, it can be concluded that cocoa bean mucilage can be used for alcoholic beverage fermentation, contributing to diversifying processing products and increasing the application potentials for cocoa.